Ulcerative Colitis Remission Status After Induction With Mesalazine Predicts Maintenance Outcomes: the MOMENTUM Trial - Rubin, David T; Bradette, Marc; Gabalec, Libor; Dobru, Daniela; Márquez, Juan; Inglis, Susi; Magee, Elizabeth; Solomon, Dory; D'Haens, Geert (Journal of Crohn's and colitis, 2016)
BACKGROUND AND AIMS: This study assessed the efficacy of maintenance treatment with multimatrix mesalazine following achievement of complete or partial remission after induction treatment with high-dose multimatrix mesalazine. METHODS: In this phase 3b/4, open-label, multicentre, prospective, single-arm study, patients with mild-to-moderate ulcerative colitis were treated with multimatrix mesalazine 4.8g/day once daily for 8 weeks [induction phase]. At Week 8, those who achieved complete or partial remission, based on predefined clinical and endoscopic criteria, were eligible to receive 12 months of multimatrix mesalazine 2.4g/day once daily maintenance therapy. The primary endpoint was the proportion of patients in complete remission at Month 12. RESULTS: A total of 717 patients received induction treatment; 25.9% and 39.3% of patients achieved complete and partial remission, respectively, at Week 8. A total of 461 patients entered the maintenance phase. The likelihood of remaining in/achieving complete remission at Month 12 was higher for patients who entered the maintenance phase in complete remission compared with those who began maintenance in partial remission [47.8% vs 26.0%; p < 0.001]. At Month 12, mucosal healing [endoscopy score ≤ 1] was demonstrated in 76.4% [139/182] and 63.5% [176/277] of those who were in complete and partial remission, respectively, at the end of induction. CONCLUSION: Patients achieving complete remission before dose reduction were more likely to remain in remission at Month 12.
Keywords: rozvrh dávkování léků; dospělí; udržovací chemoterapie; antiflogistika nesteroidní; vztah mezi dávkou a účinkem léčiva; Female; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; lidé; Drug Administration Schedule; Treatment Outcome; Aged, 80 and over; následné studie; Induction Chemotherapy; Colitis, Ulcerative; Middle Aged; indukční chemoterapie; Anti-Inflammatory Agents, Non-Steroidal; Dose-Response Relationship, Drug; prospektivní studie; Follow-Up Studies; Male; Aged; Prospective Studies; Young Adult; ulcerózní kolitida; lidé středního věku; senioři nad 80 let; mesalamin; senioři; mužské pohlaví; Mesalamine; mladiství; Maintenance Chemotherapy; Humans